Reflexively Speaking Metadiscourse in English as a Lingua Franca - Mauranen, Anna (Developments in English as a Lingua Franca [DELF], 2023)
Reflexive language - the capacity of language to speak about itself - is unique to human languages yet little is known of its use in actual dialogue. Fundamental features of language are manifest in dialogic speech and in lingua francas. Both are taken on board in this book, which radically widens our conception of reflexivity in discourse. Reflexivity, or metadiscourse, is central to successful communication. It is also vital in understanding academic argumentation, essential to academic self-understanding, and at the same time it has wide applications.